Implementasi Kebijakan Program Pengembangan Komoditas Pada Kawasan Strategi Kabupaten Di Kabupaten Bone - Rahmawati, Andi; Ansari, Muh Isa; Parawangi, Anwar (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2020)
This study purposed to analyze and describe the implementation of commodity development program policies in the strategy area at Bone Regency. The research method used  descriptive qualitative. The number of informants in the study were 15 people. Data collection used observation, interview, and documentation techniques. Data analysis were data reduction, data presentation and conclusion. The results of this study showed that the implementation of the Commodity Development Program Policy in the Strategic Area in Bone Regency was good, this was seen from the collaboration of the implementor in carrying out its duties but there were difficulties that got by the government especially in providing data and information about the superior commodities owned by the CWC. Commodity development programs in the CWC in Bone Regency especially in Palakka Sub-District, Awangpone and Barebbo greatly helped to increase the income of the local community with this program the community could find out how to develop superior commodities in the CWC region it had been  realization  in the CWC area.